Empirisme dan Rasionalitas dalam Keuangan dan Kesejahteraan pada Masa Khulafaur Rasyidin - Nawangsasi Kusuma Putri; Umi Zaidatul; Rizka Renvrita Putri; Muhammad Fathurrizqi; Rahmini Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The financial system and welfare distribution are fundamental components in ensuring the sustainability of Islamic governance, particularly during the era of the Rightly Guided Caliphs. This article aims to analyze the integration of rationality and empiricism in managing the financial system and welfare distribution under the leadership of Abu Bakr Ash-Shiddiq, Umar ibn Khattab, Uthman ibn Affan, and Ali ibn Abi Talib. Employing a literature review with a historical-descriptive approach, this study critically examines primary and secondary sources on fiscal and social policies of the period. The key findings reveal that each caliph implemented rational policies grounded in Sharia principles and structured institutional frameworks, while empirically adapting them to the diverse socio-economic realities of their societies. This dual approach-combining rational principles with practical empirical adjustments-resulted in an effective, just, and sustainable financial and welfare system. For instance, policies related to zakat collection, social assistance programs, and the management of baitul mal were designed to uphold social justice and meet the actual needs of the community. These measures demonstrated the caliphs' profound understanding of the economic and social complexities of their time, ensuring that their governance fostered public welfare and social solidarity. The findings of this study provide valuable insights for the development of modern Islamic economic policies, highlighting the importance of inclusivity and adaptability in addressing contemporary challenges.